2006
DOI: 10.1007/s00442-006-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Inversely density-dependent natal dispersal in brown bears Ursus arctos

Abstract: There is considerable controversy in the literature about the presence of density dependence in dispersal. In this study, we exploit a data series from a long-term study (>18 years) on radio-marked brown bears (Ursus arctos L.) in two study areas in Scandinavia to investigate how individual-based densities influence the probability of natal dispersal and natal dispersal distances. Cumulatively, 32% and 46% of the females and 81% and 92% of the males dispersed before reaching 5 years of age in the northern and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
162
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(179 citation statements)
references
References 47 publications
15
162
2
Order By: Relevance
“…This pattern was not observed in the nuclear genomes, and it implies a strong genetic barrier in Sweden and a strict affinity between Apennine and Alpine bears. The discrepancy between nuclear and mitochondrial data is likely explained by male-biased dispersal (43)(44)(45)(46), and the pattern of low genetic structure we observed at the Y-chromosome further supports this view (47, see SI Appendix, section S7) Until recent times, bear populations were geographically homogenized by males, but females philopatry resulted in some level of mtDNA structuring. Interestingly, habitat destruction and fragmentation has been suggested as a general factor that favors the increase of female philopatry (48,49).…”
Section: Mtdna Genomessupporting
confidence: 65%
“…This pattern was not observed in the nuclear genomes, and it implies a strong genetic barrier in Sweden and a strict affinity between Apennine and Alpine bears. The discrepancy between nuclear and mitochondrial data is likely explained by male-biased dispersal (43)(44)(45)(46), and the pattern of low genetic structure we observed at the Y-chromosome further supports this view (47, see SI Appendix, section S7) Until recent times, bear populations were geographically homogenized by males, but females philopatry resulted in some level of mtDNA structuring. Interestingly, habitat destruction and fragmentation has been suggested as a general factor that favors the increase of female philopatry (48,49).…”
Section: Mtdna Genomessupporting
confidence: 65%
“…This mechanism was suggested by spatial analyses indicating that, in northern Europe, neighbouring females have the ability to influence the likelihood of reproduction among each other [22]. This effect might be enhanced at high densities and by behavioural syndromes favouring spatial aggregation, like the repeated use of specific reproductive areas [34] and philopatric behaviour favouring that females remain close to their natal home range [35].…”
Section: (A) Reproductionmentioning
confidence: 98%
“…A common expectation regarding movement is that dispersal rates increase as environmental conditions within a population deteriorate (Travis et al 1999, Innocent et al 2010, which leads to the prediction that dispersal should increase with intraspecific density (positive density-dependent dispersal; Travis et al 1999, Innocent et al 2010. Although this prediction has been supported by several studies (Matthysen 2005, Clobert et al 2009, Meester and Bonte 2010, it has also been shown that dispersal can decrease with density (negative density-dependent dispersal; Herzig 1995, Matthysen 2005, Støen et al 2006, Meylan et al 2007). Interestingly, empirical observations suggest that, in seasonal environments, where density can operate in more than one season (Fretwell 1972, Ratikainen et al 2008, dispersal is often negatively related to density Andreassen 2005, Matthysen 2005), suggesting that temporal variation in resources (e.g., seasonality) is a key factor to understand densitydependent dispersal (Wahlströ m and Liberg 1995, Morris and Diffendorfer 2004, Matthysen 2005, Rodrigues and Johnstone 2014.…”
Section: Introductionmentioning
confidence: 99%